Peningkatan Kestabilan Berdiri Lansia Dengan Latihan Penguatan Fleksibilitas Hamstring Pada Kader Lansia - Wahyono, Yulianto; pertiwi, Jasmine kartiko (Borneo Community Health Service Journal, 2025)
The decline in physical function among the elderly often affects balance and standing stability, increasing the risk of falls and reducing quality of life. This Community Service activity aimed to improve the standing stability of the elderly through hamstring flexibility training using theraband. The program involved 35 elderly individuals in Tohudan Village, Karanganyar Regency. Measurements were conducted using the Timed Up and Go (TUG) Test and Active Knee Extension (AKE) before and after the intervention. The implementation included several stages, such as providing education, structured theraband exercises, and evaluating outcomes. Results demonstrated significant improvements in TUG Test and AKE scores after the training, indicating enhanced hamstring flexibility and standing stability. This program successfully enhanced health cadre understanding and elderly capabilities in performing recommended exercises. The initiative has potential for sustainable application in future community health meetings.